PENTINGNYA PERAN GURU SEBAGAI PEMBIMBING DALAM MENGATASI PERILAKU PERUNDUNGAN DI KELAS [THE IMPORTANCE OF THE TEACHER'S ROLE AS A GUIDE IN OVERCOMING BULLYING IN THE CLASSROOM] - Widiatmoko, Teza Friensi; Dirgantoro, Kurnia Putri Sepdikasari (JOHME: Journal of Holistic Mathematics Education, 2022)
Bullying behavior is currently very widespread in the school environment. The school as a place for students to study and pursue education becomes an environment that is no longer conducive to supporting the learning process. Therefore, this study aims to see the importance of the teacher's role as a guide in dealing with bullying behavior that occurs in the classroom. This research is qualitative descriptive research. The instruments used are observation sheets, interviews, and reflection. The conclusion obtained from this study is that the teacher as a mentor is very important in overcoming bullying behavior because the teacher acts as a role model, as well as a person who has authority in the classroom. As a supervisor the teacher pays attention to things that can be done, namely giving advice, instilling character education, as well as role models in the form of active action, namely giving motivation and exemplifying friendly and polite interaction patterns. The result is the creation of a classroom atmosphere that has good communication quality which has an impact on reducing bullying behavior in class.BAHASA INDONESIA ABSTRACT: Perilaku perundungan saat ini sangat marak terjadi di lingkungan sekolah. Oleh karena itu, sekolah sebagai wadah bagi para siswa untuk belajar dan menempuh pendidikan menjadi lingkungan yang tidak lagi kondusif dalam mendukung proses pembelajaran. Oleh karena itu, penelitian ini bertujuan untuk melihat pentingnya peran guru sebagai pembimbing dalam mengatasi perilaku perundungan yang terjadi di kelas. Penelitian ini adalah penelitian deskriptif kualitatif. Instrumen yang digunakan adalah lembar observasi, wawancara, dan refleksi. Kesimpulan yang diperoleh dari penelitian ini adalah guru sebagai pembimbing sangat penting dalam mengatasi perilaku perundungan dikarenakan guru berperan sebagai teladan sekaligus pribadi yang memiliki otoritas di dalam kelas. Sebagai pembimbing guru menaruh perhatian terhadap hal-hal yang bisa dilakukan yakni memberi nasihat, menanamkan pendidikan karakter, juga teladan dalam bentuk tindakan aktif yaitu memberi motivasi dan mencontohkan pola interaksi yang ramah dan santun. Hasilnya berupa terciptanya suasana kelas yang memiliki kualitas komunikasi yang baik yang berdampak pada menurunnya perilaku perundungan di kelas.